Effect of Hot Water Blanching on Food Processing Properties of Kelp Seedlings and in Vitro Digestibility of Its Major Nutrients - CHEN Liang, CHEN Xiaochen, DU Xiping, ZHANG Shuyu, LI Meiling, LIU Tao, NI Hui (Shipin Kexue, 2025)
In this study, we examined changes in the color, texture characteristics, nutrient composition and in vitro digestibility of kelp seedlings after hot water blanching. The results showed that after blanching, the L* value of kelp seedlings increased significantly, the b* and a* values decreased significantly, and the crispness, chewiness and resilience increased significantly. In addition, the contents of total sugar and fucoxanthin decreased significantly, while the contents of crude fiber and protein increased by 1.91 and 0.48 g/100 g, respectively. The in vitro intestinal digestibility of proteins in kelp seedings decreased significantly after hot water blanching, but the digestibility of fucoxanthin and total sugar increased. This study showed that hot water blanching improved the color, texture characteristics, crude fiber and protein contents of kelp seedlings, and promoted the digestion of fucoxanthin and total sugar, which provides a reference for the processing and utilization of kelp seedlings.